ANALISIS KANVAS MODEL BISNIS USAHA MIKRO, KECIL, DAN MENENGAH BAKMI CIKUDA - Agrina, Camelia Rizki; Prasetyo, Andreas Recki; Vidiasari, Frischa Dwi (Gapenas Publisher, 2024)
This study analyzes the Business Model Canvas (BMC) of Bakmi Cikuda Micro, Small, and Medium Enterprises, a culinary business in Jatinangor. Bakmi Cikuda is famous for its homemade recipes that produce a distinctive and authentic taste, presenting interesting menu variations such as yamin noodles, kwetiau, yahun, and other dishes that are popular with students and the local community. Despite facing challenges, such as the lack of maximizing digital technology in marketing, dependence on suppliers, and a main location that is only centered and available in the Jatinangor area, Bakmi Cikuda has succeeded in attracting customers with affordable prices and a variety of menu variations. By using the Business Model Canvas, this study identifies strategies that can be applied to optimize potential and face these challenges. The elements of the Business Model Canvas analyzed include customer segments, value propositions, distribution channels, customer relationships, sources of revenue, key resources, key activities, key partners, and cost structures. The results of the analysis show that a deep understanding of these elements can help Bakmi Cikuda to be more focused in business strategy and anticipate future challenges. The proposed strategies include strengthening digital presence, diversifying supply chains, expanding reach outside Jatinangor, addressing culinary challenges in Jatinangor, improving location and accessibility and offering affordable culinary options